2011
DOI: 10.1097/sla.0b013e318230af5a
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Double-Blind Randomized Controlled Trial of Radiofrequency Versus Laser Treatment of the Great Saphenous Vein in Patients With Varicose Veins

Abstract: ISRCTN63135694 (http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
120
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 23 publications
3
120
0
9
Order By: Relevance
“…Our study demonstrated that RFA resulted in significantly less minor complications and higher patient comfort than other EVLA techniques, consistent with the literature data. [4][5][6] Postoperative ecchymosis was more frequent in EVLA groups but postoperative pain and ecchymosis were the lowest in the RFA group, even the volume of the tumescent anesthesia was lower. This result can be explained by the effects of the laser on the vessel wall and the perivascular region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study demonstrated that RFA resulted in significantly less minor complications and higher patient comfort than other EVLA techniques, consistent with the literature data. [4][5][6] Postoperative ecchymosis was more frequent in EVLA groups but postoperative pain and ecchymosis were the lowest in the RFA group, even the volume of the tumescent anesthesia was lower. This result can be explained by the effects of the laser on the vessel wall and the perivascular region.…”
Section: Discussionmentioning
confidence: 99%
“…Despite adequate tumescent anesthesia, pain and ecchymosis can be seen after EVLA procedures. [4][5][6]10] Complications seen in our clinic have rarely been seen in terms of post-procedural complications, and no pulmonary embolism has seen. [11][12][13] Furthermore, we conducted a new operative protocol to prevent all undesired complications such as pain, bruise, and ecchymosis, which are common in almost 20 to 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations